(3GdJhRjY (B:s (3GdeaGgje(B-(3GdESJQGJjLjGJ(B-(3GdYedjGJ(B((3GdfXQjI hGdJWHjb(B) /s - (3CHhYdaI, YUGe GdOjf Cejfs ((3GdGScfOQjI(B: s (3eDSSI MhQS(B, s, 2002)
(3GSJQGJjLjGJ GdJhRjY,bfhGJ GdJhRjY,eDSSGJ GdJhRjY,JNWjW eDSSGJ GdJhRjY,GSJQGJjLjGJ GdJfSjb aj eDSSGJ GdJhRjY,EOGQI GdTQcGA deDSSI GdJhRjY(B-(3Jbjje COGA eDSSGJ GdJhRjY,GdJhRjY GdeGOjs
(3HjHdjhZQGajG (B:(3U(B.239s
Keywords: (3GdJShjbs; (3GdJhRjYs